1985
DOI: 10.1084/jem.161.4.748
|View full text |Cite
|
Sign up to set email alerts
|

Hypohaptoglobinemia associated with familial epilepsy.

Abstract: In select kindreds afflicted with familial idiopathic epilepsy, most individuals suffering seizures also have low levels of the plasma hemoglobin-binding protein, haptoglobin. This hypohaptoglobinemia may be causally associated with a tendency to develop epilepsy. Our experimental results indicate that artificially-induced hypohaptoglobinemia in mice causes retarded clearance of free hemoglobin from the central nervous system, and that such free hemoglobin may engender the peroxidation of brain lipids. We hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 28 publications
0
45
0
Order By: Relevance
“…However, intracortical injections of purified hemoglobin seem to interfere dramatically with brain physiology, as this promotes epileptic seizures (Rosen and Frumin, 1979). In agreement with this finding, reductions in plasma levels of haptoglobin are also associated with epileptic seizures (Panter et al, 1985).…”
Section: Introductionmentioning
confidence: 66%
“…However, intracortical injections of purified hemoglobin seem to interfere dramatically with brain physiology, as this promotes epileptic seizures (Rosen and Frumin, 1979). In agreement with this finding, reductions in plasma levels of haptoglobin are also associated with epileptic seizures (Panter et al, 1985).…”
Section: Introductionmentioning
confidence: 66%
“…After CNS hemorrhage, some of this Hb enters the extracellular space due to erythrocyte lysis, which may be mediated by complement activation [1]. Although small quantities of free Hb may be removed by binding to its transport protein haptoglobin [2], deposition of iron in tissue surrounding experimental hematomas is consistent with local catabolism. A growing body of evidence suggests that free heme, iron and perhaps other Hb degradation products may contribute to oxidative injury after hemorrhagic insults [3].…”
Section: Introductionmentioning
confidence: 79%
“…Increased accumulation of iron in the brain and defective antioxidant defenses have been linked to both Parkinson and Alzheimer diseases (19 ). We previously showed that hypohaptoglobinemia was associated with high incidence and frequency of seizures in patients with idiopathic familial epilepsy (20 ). Defective haptoglobin-mediated clearance of free hemoglobin from the central nervous system could lead to hemoglobindependent central nervous system damage.…”
mentioning
confidence: 99%